Environmental sustainability in the development process (UN.ECLAC Port of SpainTT, 1992)
Looks at the Regional Preparatory Meeting organized by ECLAC and the United Nations Conference on Environment and Development. Examines the role of the regional economic commissions dealing with the topics contained in Agenda 21, and the follow-up activities; the region's specific needs; and the role of ECLAC in follow-up activities.
DC